MORFOGENETIK DAERAH LUBUKSIKAPING PROVINSI SUMATERA BARAT - Lumbanbatu, Ungkap M. (Jurnal Geologi dan Sumberdaya Mineral, 2009)
The landscape of Lubuksikaping and the surrounding area is belong to the Barisan Mountain Range. In general, it had been built up by Structural Ridge, Volcanic Cone Remnant, Volcanic Cone, Structural Valley and Alluvial Plain. Those landscapes are devided into landforms based upon their genetic. It is interested to know that the landform in the western part of Structure Valley is more complexes compared to that of the eastern part. The westernpart landform is composed of several land form such as Fault Scarpment, Volcanic Cone, Volcanic Cone Remnant, Denudated hilly structure), Aluvial Fan and Aluvial Plain, while in the eastern part, the landscape mostly consists of Denudational Hill. These mean that the western part of studied area is being more dynamic. Based on those data mentioned above, it can be deduced that the landscape of this region has been influenced by volcanic and regional and or local tectonic activities, as well as by weathering, erosion, and sedimentation processes Keywords: landscape, landform, regional tectonic, local tectonic